2015
DOI: 10.1111/cen.12775
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin and dopamine receptor expression in neuroendocrine neoplasms: correlation of immunohistochemical findings with somatostatin receptor scintigraphy visual scores

Abstract: Sstr2 IHC expression and SRS are useful tools for the diagnosis and management of NENs because they display a high concordance. IHC expression of DR2 seems to be of potential clinical significance in GI-NENs tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Our observation of a high concordance between expression SSTR2, SSTR3 and SSTR5 is consistent with prior studies. 39,40 Interestingly, we found no correlation between expression of SSTR4 and other SSTRs, suggesting that SSTR4 may play different biologic role. Previous studies have reported that high expression of SSTR2 is correlated with lower MKI67 (Ki-67) labeling index in NETs, though many of these studies included both low and high grade tumors, 22,33,38,4144 Our study was limited to well differentiated NETs.…”
Section: Discussionmentioning
confidence: 60%
“…Our observation of a high concordance between expression SSTR2, SSTR3 and SSTR5 is consistent with prior studies. 39,40 Interestingly, we found no correlation between expression of SSTR4 and other SSTRs, suggesting that SSTR4 may play different biologic role. Previous studies have reported that high expression of SSTR2 is correlated with lower MKI67 (Ki-67) labeling index in NETs, though many of these studies included both low and high grade tumors, 22,33,38,4144 Our study was limited to well differentiated NETs.…”
Section: Discussionmentioning
confidence: 60%
“…The percentages of NETs that were sst 2a positive on SRS but sst 2a negative on IHC on tumor samples (sst 2a : IHC-/SRS+) varied between 0 and 15% [10,25,26]. Other sst receptor subtypes than sst 2 showed no significant relationship between IHC on tumor samples and in vivo SRS uptake on OctreoScan® [10,25,26]. Since these receptor subtypes are less frequently expressed on GEP-NETs as compared to sst 2a , we focused only on sst 2a IHC in our study [1,2,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also evaluated the concordance between immunohistochemistry and SRS results, especially SSTR2a. These authors reported that the SSTR2a and SRS findings correlated in 82.7% of their 81 neuroendocrine neoplasms [13]. Other studies noticed that evaluation of the expression of SSTR3 and SSTR5 did not provide further concordance with the SRS findings obtained from SSTR2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…SRS is clinically very useful, though few reports compare the pathologic expression of the SSTR with SRS [13]. In addition, SRS was not approved in Japan until recently.…”
Section: Introductionmentioning
confidence: 99%